Perlindungan Hukum Terhadap Investor Pemegang Obligasi Atas Gagal Bayar Yang Dilakukan Oleh Emiten Selama Pandemi Covid-19 - Humaira Nadhifa; Lastuti Abubakar; Tri Handayani (Widya Yuridika, 2022)
The development of the Indonesian Capital Market is currently running very rapidly. The rapid development Indonesian Capital Market can’t be separated from the role of Investors and Issuers as the main actors in the capital market. Bond as one of the investment instrument in Indonesian Capital Market which currently circulating in line with high demand among investor considering bond have lower risk than other capital market instruments. However, investing in bond is not without risk, because Issuer may fail to pay their obligation. The Coronavirus Disease 2019 (Covid-19) Pandemic has caused bond default rates to increase. Such condition can lead to a crisis of Investors confidence in Indonesian Capital Market. Therefore, this study aims to find out and understand the form of legal protection for Investors who suffer losses due to default during Covid-19 Pandemic and the legal actions that can be taken by Investors for losses arising from default. The research method used is normative juridical with descriptive analytical research specification. Based on the Indonesian Civil Code and Indonesian Capital Market Law, it can be concluded that the Issuer who issue bond is responsible for paying bond interest and returning the principal of the bond loan on the maturity date to Investors. Bond default give Investors the right to demand the return of their rights to bond interest and to the principal of maturing bond through the Trustee. Legal actions that can be taken by bondholders are internal dispute settlement, external dispute settlement through Integrated Alternative Dispute Resolution Institution, or through litigation.